The Hijab as Border of Cloth: An Ecological Systems Theory Perspective - Prinsloo, Gert T. M.; Prinsloo, Reineth C. E.; Bin Nafisah, Latifah A. A. (Journal for Semitics, 2019)
Using ecological systems theory to understand the systemic interactions in the context of Islam is not an extensively researched topic. In view of this, ecological systems theory is used in this article to argue that the social interaction of an individual Muslim female deliberately donning the hijab should be interpreted and evaluated in the context of Islam as an ecological system. Islam is analysed as an ecological system in which each part of the system is influenced by all other parts, but in turn also influences all other parts. There are borders between the various parts of the system, but these borders are permeable from the inside and from the outside. These principles are applied to every Muslim female who chooses to don the hijab. She becomes an integral and indispensable part of Islam as a system. She is influenced by every part of the system, and in turn influences every part by her conscious choice to give visual expression to her religious identity. Awareness of the mutual interactions between an individual Muslim female and all other constituent parts of her religion allows for a contextual and holistic analysis of the hijab as religious and cultural phenomenon. The hijab functions as a border of cloth demarcating the Muslim female body as sacred space in space as she interacts with and within her micro-, meso-, exo-, macro-, and chronosystems.